Performance Comparison of VSI Switches Faults Analysis Using STFT and S transform - Manap, Mustafa; Abdullah, Abdul Rahim; Saharuddin, N. Z.; abidullah, Noor Athira; ahmad, nur sumayyah; JOPRI, MOHD HATTA (Trans Tech Publications, Switzerland, 2015)
Switches fault in power converter has become compelling issues over the years. To reduce cost and maintenance downtime, a good fault detection technique is an essential. In this paper, the performance of STFT and S transform techniques are analysed and compared for voltage source inverter (VSI) switches faults. The signal from phase current is represented in jointly timefrequency representation (TFR) to estimate signal parameters and characteristics. Then, the degree of accuracy for both STFT and S transform are determined by the lowest value of mean absolute percentage error (MAPE). The results demonstrate that S transform gives better accuracy compare to STFT and is suitable for VSI switches faults detection and identification system.